MENGASUH DAN MENDIDIK ANAK DALAM KELUARGA - sahri (Universitas Nahdlatul Ulama Sunan Giri, 2020)
Children are entrusted by God to humans who must be guarded, cared for, nurtured, guided, raised, educated, fulfilled, schooled, married and established so that they become independent when they are released. Nurturing and educating wholeheartedly is very necessary in the family for their children. The family is a figure and model that is the first in the process of the educational process. Children will not be much different from the behavior and behavior that has been done by the family. Therefore, being a parent must be able to transfer various kinds of information and characters that are good for children's development. So that they have the responsibility of caring for and educating children in the family to become children who are expected and useful for religion, the homeland and the nation.